Ekonomizacja administracji publicznej : aspekt regionalny i systemowy - Kalisiak-Mędelska, Magdalena; Dąbrowski, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article contains a presentation of systemic terminology. An attempt was made in the article to asses possibilities of using the systemic analysis in regional studies.The political and economic changes which have taken place in the world economy affect economic systems in many countries. Many companies act according to free-market economy and so does public administration. It seems to be not only a local authority but also "the creator" of many goods for its customers and must use methods typical of business. Despite this, public administration is still a special state structure designed to complete a wide range of public tasks. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 221-232